Caracterización del agente patógeno botritys sp en el cultivo de Statice (Limonium Sinuatum) en la empresa Florícola San Isidro labrador ¨FLORSANI¨ Parroquia Malchiguí Cantón Pedro Moncayó Provincia de Pichincha - Perugachi Garcito, Inti Rumiñahui (2019)
VII. SUMMARY Within the investigation it is observed that the cultivation of Statice (Limonium Sinuatum) gives greater ease of less labor, in addition to having a great combination with other crops such as: solidarity, aster, hypericum, and in others and thus obtain other markets with floral arrangements Not only solid processed bouquets. It is for this present investigation on “Characterization of the Botriys sp pathogen in the Florícola San Isidro Labrador ¨FLORSANI¨ Parish Malchiguí Canton Pedro Moncayó Pichincha Province. To generate great profit within the company without major problems and customer complaints when this product was sent. The cultivation of Statice (Limonium Sinuatum) is very demanding irrigation management so as not to transmit the pathogen so easily. Methods that were used for the research topics an interview was issued directly to the head of area and the disease that caused the greatest problem was determined, is the Botritys sp in the floral spike affecting the quality for the export of plant material with confidence for its clients. According to the results, it indicates that the symptomatology is easier to know in color, that it is transmitted by which it has a lot of culture in the same area, in addition to the favorable conditions of the pathogens is humidity and the controls that are used is the chemical control by Its greater efficiency. It is also recommended to use other methods of control, application of irrigation less frequently to avoid obtaining a greater presence and favorable condition of the pathogen for its development. Keywords: Agent, Pathogen, Botritys, Statice.